Refuse Derived Fuel (RDF) dari Sampah Perkotaan dengan Proses Biodrying: Review - Chaerul, Mochammad; Wardhani, Annisa Kusuma (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
The utilization of waste into fuel (Refuse Derived Fuel, RDF) is an alternative to overcome the problem of municipal solid waste (MSW). Many processes can be applied to produce RDF including through biodrying process. Biodrying is a part of Mechanical-Biological Treatment (MBT) aiming to reduce water content in the waste by utilizing heat generated from microorganism activities while degrading organic matter in the waste, thus the calorific value will increase. The paper aims to make a review from various research papers on biodrying process published in scientific journals, so it becomes one of reference on further research on biodrying process by considering the characteristics of waste in Indonesia. The review has been conducted by focusing on several important aspects on the research such as operation principle, reactor design configuration, parameters to be examined, and the characteristics of feed and product.